Pengelolaan ZIS Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat (Studi Pada Baznas Kabupaten Jombang) - Labuh Inderayana Eka Sakti; A'rasy Fahrullah (Universitas Negeri Surabaya, 2022)
Welfare is desired by every individual and realized through efforts such as minimizing poverty and improving health as well as education. Law No. 23 of 2011, which regulates zakat management, has a significant impact on Baznas in managing zakat, infaq, and sadaqah at the national level. In realizing these objectives, Baznas Jombang prepares 5 programs to be distributed through productive and consumptive assistance to improve mustahiq welfare. This research is qualitative research that intends to analyze the management of zakat, infaq, and sadaqah in improving the welfare of the community. The results of this study show that the management of zakat, infaq, and sadaqah in improving the welfare of the community in Baznas Jombang Regency manifests in the form of the Jombang Berdaya and Jombang Sehat program, where a productive economy to develop small micro businesses and consumptive assistance by improving the standard of living of children with special needs were discovered.